Heat-resistant bacterial phytase in broiler pelleted diets - Carlos,TC de F (2015)
The objective of the study was to evaluate the effects of a heat-resistant bacterial phytase added to pelleted diets on mineral digestibility, live performance, carcass traits, and bone quality of broilers. Three treatments were evaluated: Positive control; negative control, with 0.10 points reduction in calcium level and 0.15 points reduction in available phosphorus level; and negative control + phytase at 500 FTU/kg. Mineral digestibility and bone quality results demonstrated that the evaluated phytase resisted pelleting as it increased the utilization of the minerals present in the diet.